KEBIJAKAN HUKUM PIDANA MEMPERTAHANKAN JENIS PIDANA MATI (STUDI KASUS PEMBUNUHAN BERENCANA DISERTAI MUTILASI KORBAN) - Yudiantari Darmadi, A.A. Sagung Mas (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The research was policy of criminal law maintains kind of death penalty (the case study of plan murder while mutilates the victim), aims to describe and analyze the existence of the death penalty to the crime of plan murder. In addition, this study also aims to determine policies of criminal law related to death penalty for the crime of plan murder accompanied by mutilation as an aggravating. The method used in this research was conducted normatively by reviewing the primary and secondary which was collected based on collecting method of normative law and for the technique of collecting its legal entity were used documenter technique i.e the technique to analyze and collect on various documents that already exists by applying some kind of approach, namely, the approach of legislation, and analytical approaches. The analysis of research was presented in form of descriptive-analytical, systematic, constructive and argumentative. The death penalty against the crime of murder is still maintained and in force today in Indonesia, as contained in the provisions of Article 340 of the Criminal Code. Capital punishment are recognized in the criminal offense of premeditated murder, but the death penalty was alternatifed with other criminal types namely life imprisonment and a maximum of 20 years. Death penalty imposed in the case of things that are burdensome. By it did not published things that incriminate a crime in the Criminal Code, the judge only include things that are burdensome and ease generally. This certainly can not be released that the provisions of Article 197 paragraph (1) Criminal Code incriminating things was imperatively. Regarding the criminal law policy relating to the death penalty for the crime of murder was listed in Article 581 of the Criminal Code. In this case, the RUU KUHP did not include the Criminal Code specifically mutilation as a criminal aggravating reasons, however when seen from the provisions of Article 55 paragraph (1), the mutilation may be a motive and purpose of committing a crime (letter b); how committed the crime (letter e); as well as the attitudes and actions of after committing a crime (letter f).
Keywords: Criminal Law; Death Penalty; Policy